Selection of materials using analytical hierarchy process and Pugh's selection method - Arep @ Ariff, Hambali; Salit, Mohd Sapuan; Ismail, Napsiah; Yusoff, Nukman (2009)
There is an increased selection of right materials to be determined at the early stage of design process. The growing number of articles on materials selection literature is an indication of the importance of the right material for a given application. Inappropriate selection of materials always leads to huge cost involvement and ultimately drives towards premature component or product failure. This paper presents a literature review of analytical hierarchy process and Pugh’s selection process to assist material engineers to determine the most appropriate material. The comparison between analytical hierarchy process and Pugh’s selection method is described in this paper. In order to compare both of these methods, various composite materials of automotive bumper beam have been considered as a case study. It is showed that materials selection using analytical hierarchy process plays a very significant role instead of using Pugh’s selection method.